Hypofractionated versus conventional radiotherapy for head-and-neck cancer: A systematic review and meta-analysis - Arnab Roy; Shambodeep Chatterjee; Priyanka Biswas (Annals of Oncology Research and Therapy)
OBJECTIVE: The objective of the study was to compare the efficacy and toxicity of hypofractionated radiotherapy versus conventional fractionated radiotherapy in head-and-neck cancer patients using meta-analysis. METHODS: PubMed, Embase, Cochrane CENTRAL, and ClnicalTrials.gov were searched to identify the trials comparing conventionally fractionated radiotherapy versus hypofractionated radiotherapy in head-and-neck cancer patients. Compete response (CR) was the primary endpoint, and partial response (PR), overall survival (OS), disease-free survival (DFS), progressive disease (PD), stable disease (SD), local regional recurrence (LRR), acute skin toxicity, and mucositis were the secondary endpoints. This study is registered in PROSPERO (CRD42024513677) and includes the PRISMA checklist also. RESULTS: This meta-analysis included six controlled clinical trials with 310 head-and-neck cancer patients. No significant differences in CR were revealed by this meta-analysis performed by us (odds ratio [OR] =0.94, 95% confidence interval [CI] =0.51–1.71, P = 0.83), PR (OR = 0.97, 95% CI = 0.48–1.97, P = 0.93), LRR (OR = 1.45, 95% CI = 0.71–2.95, P = 0.31), DFS (OR = 0.87, 95% CI = 0.20–3.83, P = 0.86), OS (OR = 0.83, 95% CI = 0.16–4.40, P = 0.83), SD (OR = 1.82, 95% CI = 0.45–7.36, P = 0.40), PD (OR = 0.79, 95% CI = 0.18–3.46, P = 0.75), Acute skin toxicity (OR = 1.75, 95% CI = 0.61–5.05, P = 0.30), and mucositis (OR = 2.9, 95% CI = 0.35–24.25, P = 0.33 between the two groups. CONCLUSION: Our study’s results indicate that the efficacy and safety of hypofractionated radiotherapy do not notably differ from those of conventional fractionated radiotherapy.